Amphibians breeding in refuge habitats have larvae with stronger antipredator responses. (August 2016) - Manenti, Raoul; Melotto, Andrea; Denoël, Mathieu; Ficetola, Gentile Francesco
Abstract : Antipredator responses are a key determinant of the successful persistence of prey, and behavioural modifications are a frequent antipredator strategy. However, conspecific populations often inhabit heterogeneous environments. This can determine local adaptations, and might also induce variation in antipredator responses. Nevertheless, there is limited information on whether heterogeneity of predation risk among populations determines variation in antipredator response. Here we studied the fire salamander, Salamandra salamandra, a species that can breed in both surface streams and caves, habitats that are predator-rich and predator-free, respectively, and measured differences in antipredator responses across populations with different predation risk. We combined field surveys and laboratory experiments to understand the role of predation risk on the activity patterns of larvae, while measuring behavioural differences between populations. We reared larvae from different habitats in safe and risky conditions and tested their response to predator cues before and after rearing. In the field, predation risk was much higher in surface streams than in caves; larvae moved more in the absence of predators and when the light intensity was low. During laboratory experiments, larvae were less active if reared in risky conditions, but cave larvae showed a stronger response to risk than stream larvae. Therefore, larvae from sites without predators showed higher antipredator responses than those from risky habitats. This response fits the predictions of the risk allocation model, in which prey from habitats with a high background level of risk need to be active even when predators are present, to satisfy their energetic demands. Our findings show that antipredator behaviour may differ strongly between populations and stress the importance of integrating this variability in studies on predatory responses. Highlights: We compared antipredator behaviour in salamander populations from caves and streams. Predation risk is lower in caves than in surface streams and pools. Light exposure and predator presence reduce salamander larvae activity in the wild. Cave-born salamander larvae show more pronounced antipredator behaviour. Heterogeneity of predation pressure determines intraspecific behavioural variation.